IMPLEMENTATION OF THE CONCEPT AND DESIGN OF INDEPENDENT CURRICULUM MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION - Sholeh, Lukman (Universitas Nurul Jadid, 2022)
The focus of this research is to challenge the Implementation of the concept and design of Independent Curriculum Management in improving the Quality of Education at the junior high school level. The methodology or approach used in this paper uses a library research method or procedure. At the same time, data collection is carried out by studying and exploring several journals, books, and documents (both printed and electronic) as well as other sources of data and or information that are considered relevant to the study; the purpose of this study is to find out the Implementation of the concept and design of Independent Curriculum Management in improving the Quality of Education, The results of this study concluded that the Implementation of the idea of independent curriculum education in improving the quality of education integrates literacy skills, knowledge skills, skills and attitudes as well as mastery of technology. The independent curriculum is a program expected to restore learning, which offers three characteristics, including project-based learning for developing soft skills and attributes following the profile of Pancasila students, learning on essential materials, and a more flexible curriculum structure.